Tandem Dihydroxylation, Hemiketalization and Conjugate Addition Leading to a Singly Anomeric Spiroketal - Davy, Jason A.; Moreau, Benoît; Wulff, Jeremy E. (Synthesis, 2012)
A novel, highly stereoselective tandem dihydroxylation, hemiketalization and conjugate addition reaction is reported that transforms a linear meso-functionalized bis-enone into a substituted singly anomeric spiroketal, effectively controlling six stereocenters in a single operation. As part of an effort to explore the thermodynamic consequences of establishing the singly anomeric spiroketal in this system, the assembly of a related fully anomeric spiroketal possessing an unusual ketal-spiroketal-ketal framework is demonstrated.
Keywords: tandem reaction; spiro compounds; dihydroxylation; stereoselective synthesis; enones